Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament Berbantuan Media Scrapbook Dilengkapi Question Card terhadap Hasil Belajar Siswa - Intan Ana Jawa; Vidriana Oktoviana Bano; Yohana Njoeroemana (Jurnal Pelita: Jurnal Pembelajaran IPA Terpadu, 2025)
This study aims to determine the effect of the Team Games Tournament (TGT) cooperative learning model assisted by scrapbook media equipped with question cards on students’ learning outcomes at SMPN Satap Padammu. The urgency of this research is based on the importance of implementing innovative learning models that can enhance students’ active participation, motivation, and academic achievement. The TGT model provides opportunities for students to learn through teamwork and healthy competition, while the use of scrapbook media and question cards is expected to strengthen conceptual understanding through visual and interactive activities. Thus, this research contributes to the development of creative and effective learning strategies to improve the quality of teaching and learning processes in secondary schools. This study employed a quasi-experimental design with a quantitative associative comparative approach. The research design used was the Nonequivalent Control Group Design, involving two classes: class VIII IPA A as the control group with 29 students and class VIII B as the experimental group with 26 students, totaling 55 students at SMPN Satap Padammu. Data collection instruments included interviews, observations, and written tests in the form of pretests and posttests to measure students’ learning outcomes before and after the treatment. The collected data were analyzed using a paired sample t-test to determine the difference in learning outcomes before and after implementing the learning model. The analysis results showed that the Asymp. Sig (2-tailed) value was 0.001 < 0.05, indicating that H? was rejected and H? was accepted. This means that the implementation of the Team Games Tournament (TGT) learning model assisted by scrapbook media and question cards had a significant positive effect on students’ learning outcomes.